Evaluation of the Role and cost-effectiveness of End-Of-Life Orthopaedic Interventions in Cancer Patients with Skeletal Metastases to the Hip. Issue 2 (June 2013) - Singh, Gurpal; Lim, Chin Tat; Jonathan, Tan Jiong Hao; Nathan, Saminathan Suresh
This study aimed to evaluate the effect of hip reconstruction on patients with skeletal metastases to the hip. We investigated the effect of hip reconstruction on quality of life and ambulatory status, as well as cost-effectiveness of hip reconstruction in this group of patients.